Canadian Network for Mood and Anxiety Treatments (CANMAT) and International Society for Bipolar Disorders (ISBD) collaborative update of CANMAT guidelines for the management of patients with bipolar disorder: update 2013. (12th December 2012) - Yatham, Lakshmi N; Kennedy, Sidney H; Parikh, Sagar V; Schaffer, Ayal; Beaulieu, Serge; Alda, Martin; O'Donovan, Claire; MacQueen, Glenda; McIntyre, Roger S; Sharma, Verinder; Ravindran, Arun; Young, L Trevor; et al.
<x xml:space="preserve">Abstract</x> Yatham LN, Kennedy SH, Parikh SV, Schaffer A, Beaulieu S, Alda M, O'Donovan C, MacQueen G, McIntyre RS, Sharma V, Ravindran A, Young LT, Milev R, Bond DJ, Frey BN, Goldstein BI, Lafer B, Birmaher B, Ha K, Nolen WA, Berk M. Canadian Network for Mood and Anxiety Treatments (CANMAT) and International Society for Bipolar Disorders (ISBD) collaborative update of CANMAT guidelines for the management of patients with bipolar disorder: update 2013. Bipolar Disord 2012: 00: 000–000. © 2012 John Wiley & Sons A/S.Published by Blackwell Publishing Ltd. The Canadian Network for Mood and Anxiety Treatments published guidelines for the management of bipolar disorder in 2005, with updates in 2007 and 2009. This third update, in conjunction with the International Society for Bipolar Disorders, reviews new evidence and is designed to be used in conjunction with the previous publications.The recommendations for the management of acute mania remain largely unchanged. Lithium, valproate, and several atypical antipsychotic agents continue to be first‐line treatments for acute mania. Monotherapy with asenapine, paliperidone extended release (ER), and divalproex ER, as well as adjunctive asenapine, have been added as first‐line options.For the management of bipolar depression, lithium, lamotrigine, and quetiapine monotherapy, as well as olanzapine plus selective serotonin reuptake inhibitor (SSRI), and lithium or divalproex plus SSRI/bupropion remain first‐line options. Lurasidone monotherapy and the combination of lurasidone or lamotrigine plus lithium or divalproex have been added as a second‐line options. Ziprasidone alone or as adjunctive therapy, and adjunctive levetiracetam have been added as not‐recommended options for the treatment of bipolar depression. Lithium, lamotrigine, valproate, olanzapine, quetiapine, aripiprazole, risperidone long‐acting injection, and adjunctive ziprasidone continue to be first‐line options for maintenance treatment of bipolar disorder. Asenapine alone or as adjunctive therapy have been added as third‐line options.